Directed reading thinking activity to improve students, reading comprehension skill - Fajar Mahdi (ELT Forum: Journal of English Language Teaching, 2025)
Direct reading and thinking strategy or DRTA (Directed Reading Thinking Activity) is a strategy to train students to concentrate and think hard to understand the contents of the reading seriously. This strategy focuses on students' engagement with the text because students predict and prove it when they read. Using a qualitative descriptive design, this study was conducted through direct observation of the learning process and in-depth interviews with teachers. Strategy Direct this Reading Thinking Activity (DRTA) was implemented in several stages of learning pre-reading stage, reading stage, and post-reading stage. The strategy is designed to ask students to predict reading content and paragraph content based on the knowledge and experience students already have, think about predictions while reading and test/revise related readings. In addition, students responded positively to the implementation of DRTA. Many students feel more engaged, motivated, and able to deepen reading comprehension compared to conventional teaching methods. The conclusion, the DRTA strategy is very effective in being used qualitatively to improve students' reading comprehension and hone critical and reflective thinking skills. In order to obtain optimal results, intensive guidance from the teacher is needed to encourage student involvement at every stage. The results of this study provide guidance for teachers to integrate critical thinking approaches in English language teaching.